The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0206457
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception of pastoral community members about brucellosis as a cause of abortion in animals and its zoonotic importance in Amibara district, Afar Region, Ethiopia

Abstract: Sero-epidemiological studies of brucellosis in the Afar Region showed that the disease is prevalent in livestock. However, there is little information regarding the pastoral community members’ awareness about brucellosis as a cause of abortion in animals and its zoonotic importance. In this study, we assessed knowledge and perception of pastoral community members about brucellosis as a cause of abortion in animals and its zoonotic importance in Amibara district, Afar Region, Ethiopia. Between October and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The low awareness of respondents could be attributed to a lack of adequate understanding of livestock diseases and the low proportion of farmers that received formal education in the study area, which is in agreement with the study report in Pakistan (Arif et al 2017). Similarly, in the present study, fewer respondents were aware about the risk of transmission of any disease from animals to humans, which is in line with the findings in Ethiopia (Legesse et al 2018;Zewdie et al 2018) and elsewhere (Ndengu et al 2017;Zhang et al 2019). This suggested that improving LFs' knowledge on animal disease and the likely modes of transmission could help to reduce disease risk in humans.…”
Section: Discussionsupporting
confidence: 90%
“…The low awareness of respondents could be attributed to a lack of adequate understanding of livestock diseases and the low proportion of farmers that received formal education in the study area, which is in agreement with the study report in Pakistan (Arif et al 2017). Similarly, in the present study, fewer respondents were aware about the risk of transmission of any disease from animals to humans, which is in line with the findings in Ethiopia (Legesse et al 2018;Zewdie et al 2018) and elsewhere (Ndengu et al 2017;Zhang et al 2019). This suggested that improving LFs' knowledge on animal disease and the likely modes of transmission could help to reduce disease risk in humans.…”
Section: Discussionsupporting
confidence: 90%
“…Even though the majority of the respondents reported sheep and goats' abortion during the two years before the interview, the causes of abortion, their transmission modes, preventive actions, and their public health significance are rarely known and understood by farmers and pastoralists. Previous studies in Ethiopia [ 36 , 64 ] and elsewhere [ 43 , 65 ] have also described knowledge gap on the public health risk of zoonotic abortion-causing agents such as Brucella, Leptospira, Toxoplasma, Chlamydophila and Coxiella. This low level of awareness of zoonotic diseases among communities may be the consequence of low information and awareness about the burden and transmission of the disease among veterinary and public health professionals, inaccessibility of public health centres, and lack of trained manpower in health education [ 21 , 43 , 51 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many studies show significant knowledge of brucellosis among rural and urban populations in developing countries; with between 40 and 100% of populations reporting awareness of the disease and its clinical presentations [8,[12][13][14]. However, few studies have been carried out among nomadic pastoralist communities residing in underdeveloped remote and arid areas and deriving livelihood primarily from rearing livestockwhere infection risk is likely elevated [13,15].…”
Section: Introductionmentioning
confidence: 99%